(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence in Italy of the mite Centrouropoda almerodai Wisniewski and Hirschmann 1992 was noted for the first time. It is a phoretic species associated with the curculionid Rhynchophorus ferrugineus (Olivier). The latter recently introduced in the Mediterranean area, it has caused serious damages to pahn trees belonging to the Phoenix genus in Northern Africa, Spain, Greece and Italy.